#TITLE_ALTERNATIVE# - HERDITA (NIM 17303032); Pembimbing: Dr. Pribadi Widodo, M.Sn., PATRICIA
The traditional architecture of Indonesia is rich by its cultural diversity from every island on Indonesian territory with each tradition inheritance; one of the islands is Bali. The Balinese people way of life is based on the philosophy derived from the ancestors from time to time, and represented by their culture in this case is the traditional architecture. Hindu is the major religion in Bali and its philosophy has adopted for the Balinese people way of life. These philosophies are portrayed in their everyday life and their culture, such as traditional architecture and the example is Puri. The basic belief of Hindu is to keep the balance between the human presence in the universe and Ida Sang Hyang Widhi. Hindu uses many symbols to reflect their beliefs to the God and to help them achieve the highest sacred mind about their presence. One of the symbol is color, but whether the use of color in Hindu as a symbol affected the use of color in Balinese traditional architecture, that is the main idea of this research about. The result is that the use of color in Hindu affects some of the use of color in Balinese traditional architecture. The relation was found between the philosophy of the color in Hindu and the presence of the color in the architecture. Hopefully the result of this research may help the designer and architect planning the color for the Balinese style building design. On the other hand, may this research could be a start for the next further research.